If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 6y = -14 Solving 2x + 6y = -14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 2x + 6y + -6y = -14 + -6y Combine like terms: 6y + -6y = 0 2x + 0 = -14 + -6y 2x = -14 + -6y Divide each side by '2'. x = -7 + -3y Simplifying x = -7 + -3y
| 5-7x=61+t | | 2.1y-1.1y+2.3=-7.7 | | 54-3x=-22 | | (x-1)*2-8=0 | | 4*x=4*2+x*2 | | 15v+3v+-4v=-16 | | 2-6x=10x | | 70=3*(4+y) | | -6-2n=n+8-5n | | Y=125+3x(12-2y) | | 10a^2-10-20=0 | | 10a^2-10a-20=0 | | 2(h-1)+20=-4 | | 3(3x+2)=15 | | 7x-4=7x-4 | | 3x^2-6x^3=0 | | 19x^2-48x=27 | | 72u^2-98v^2= | | 8+25+5a=35-3b+12 | | 4.5y=2(y-6.28) | | (r+4)*2-25=0 | | -200=130x+200y | | (r+4)2-25=0 | | (9+v)(4v+2)=0 | | 6x^2=-240+84x | | 59=5+6n | | 4x-93=-3x+9 | | -6x^2+37x-45=0 | | 8+25+5y=35-3y+12 | | 22.5=7.5(k-5) | | 26=6-5r | | 25+5y=35-3y |